2022
DOI: 10.21002/amj.v14i1.1149
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of Repurchase Intention During The Corona Pandemic: An Examination of Gender Difference

Abstract: Manuscript type: Research Article Research Aims: To examine the drivers of repurchase intention and test the difference between male and female consumers on the relationships between consumption value, satisfaction, and repurchase intention. Design/methodology/approach: This study employs a descriptive research design. Data were collected from 214 consumers who purchased food from the restaurant using the online application. Structural Equation Modeling has been employed to test the proposed hypotheses. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The findings substantiate the evidence that there is a difference between males and females (Ozdemir et al, 2012). Moreover, Nasution et al (2022) investigated repurchase intention among restaurant customers; the results showed that male and female customers have different perceptions of RI. Additionally, Beldona and Namasivayam (2006) found that women are less likely to revisit businesses that employ higher prices based on demand fluctuations.…”
Section: Discussion and Recommendationssupporting
confidence: 79%
“…The findings substantiate the evidence that there is a difference between males and females (Ozdemir et al, 2012). Moreover, Nasution et al (2022) investigated repurchase intention among restaurant customers; the results showed that male and female customers have different perceptions of RI. Additionally, Beldona and Namasivayam (2006) found that women are less likely to revisit businesses that employ higher prices based on demand fluctuations.…”
Section: Discussion and Recommendationssupporting
confidence: 79%
“…Healthcare services are a top priority for the public, and the quality of services significantly affects consumers' physical and mental well-being. With increasing purchasing power, consumers prefer healthcare institutions providing superior services, making this crucial in the competitive healthcare industry (Wahyuningsih et al, 2022). Consumers are more aware of healthcare service quality, forming judgments based on their past experiences (Hannawa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer satisfaction, combined with service quality, significantly influences the intent to revisit hospitals. Satisfaction reflects positive sentiments from consumer assessments of their experiences relative to expectations (Wahyuningsih et al, 2022). In serviceoriented industries, it plays a crucial role in evaluating service efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation